The Influence of Principal Management and Teacher Work Discipline on the Performance of High School Teachers in the District Pangururan, Samosir Regency - Karolina Br Siahaan; Rencan C. Marbun; Pardomuan Simanullang (Indonesian Journal on Education (IJoEd), 2026)
This study aims to determine 1) the influence of Principal Management on the performance of public high school teachers in Pangururan District, Samosir Regency; 2) the influence of Teacher Work Discipline on the performance of public high school teachers in Pangururan District, Samosir Regency; and 3) the simultaneous influence of Principal Management and Teacher Work Discipline on the performance of public high school teachers in Pangururan District, Samosir Regency. This study was conducted using a quantitative survey method. The population was 82 public high school teachers in Pangururan District, Samosir Regency. The sample was a saturated sample, representing the entire population. Data were collected using a closed questionnaire consisting of 20 items to measure variable Y (Teacher Performance), 20 items for variable X1 (Principal Management), and 20 items for variable X2 (Teacher Work Discipline), resulting in a total of 60 items. Before being used on actual respondents, the instrument was first tested on 30 teachers of SMA Negeri 1, Ronggurnihuta District, Samosir Regency. The results of the instrument trial showed that all questionnaire items were valid and reliable. Data analysis techniques were carried out using descriptive analysis with variable categorization and parametric statistical analysis using simple and multiple linear regression equation tests, correlation and coefficient of determination tests, t-tests, and F-tests. The results of the data analysis show that: 1) there is a positive influence of Principal Management on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 39.6%, a strong correlation value of 0.629, with a linear equation Y = 32.623 + 0.513X1 and t count = 7.240> t table (n-2 = 80) = 2.000; 2) There is a positive influence of Teacher Work Discipline on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 340%, a strong correlation value of 0.583, with a linear equation Y = 28.608 + 0.543X2 and tcount = 6.421> ttable (n-2 = 80) = 2.000 and 3) There is a positive influence of Principal Management and Teacher Work Discipline simultaneously on the performance of State Senior High School teachers in Pangururan District, Samosir Regency with a contribution of 49%, a strong correlation value of 0.700, multiple linear equation Y = 21.660 + 0.366X1 + 0.331X2 and Fcount = 37.961> Ftable (k-1, n-k; 2.80) = 3.15. Thus the research hypothesis is accepted.